International Relations Theory - McGlinchey, Stephen; Walters, Rosie; Scheinpflug, Christian (Open textbook library., 2017)
This book is designed as a foundational entry point to International Relations theory – structured to condense the most important information into the smallest space and present that information in an accessible manner. The first half of the book covers the theories that are most commonly taught in undergraduate programmes. The book then expands to present emerging approaches and offer wider perspectives. Each chapter sets out the basics of a theory whilst also applying it to a real-world event or issue, creating a lively, readable and relevant guide that will help students to see not only what theories are – but why they matter.